THE EFFECT OF RETURN ON EQUITY (ROE) AND DIVIDEND POLICY ON STOCK RETURNS IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2020–2024 - Resti Alfatin; Rakha Rajendra; R. Aryanti Ratnawati; Kusmadi Kusmadi (Multifinance, 2026)
This study aims to analyze the effect of Return on Equity (ROE) and Dividend policy projected by Dividend Payout Ratio (DPR) on Stock Returns in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). The data used in this study are quarterly panel data from 7 companies during the period 2020Q1 to 2024Q4, resulting in a total of 140 observations. The analysis method used is panel data regression with the Chow test and Hausman test stages for model selection. Classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) are also conducted to ensure the validity of the model. The results of this study indicate that the Fixed Effect Model (FEM) is the chosen model based on a series of tests. The classical assumption test indicates that the model residuals are normally distributed, proven to be free from multicollinearity, heteroscedasticity, and autocorrelation problems. Simultaneously, ROE and dividend policy (DPR) have a significant effect on stock returns. Partially, Return on Equity (ROE) is found to have a negative and significant effect on Stock Return, while Dividend Payout Ratio (DPR) has a positive and significant effect on Stock Return. These findings provide implications for investors in making investment decisions and for company management in formulating financial policies.